1989
DOI: 10.1038/eye.1989.116
|View full text |Cite
|
Sign up to set email alerts
|

Pseudoexfoliation glaucoma in Greece

Abstract: SummaryPseudoexfoliation glaucoma is commonly seen in Greece� bowever there is little data concerning the prevalence and characteristics of this disorder. Patients undergoing trabeculectomy for open angle glaucoma were investigated both by the appraisal of the case notes and by re-examination. The prevalence of pseudoexfoliation glaucoma in this population was found to be 87.8 %. The characteristics of this disease process in the population studied are discussed. These findings indicate that pseudoexfoli ation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
23
0
14

Year Published

1991
1991
1999
1999

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 35 publications
2
23
0
14
Order By: Relevance
“…Two studies where the data were population corrected and subsequently compared with age matched controls, show females being affected by the disorder more frequently than males (Aasved 1969;Hiller et al 1982). However, this preponderance of females has not been confirmed in other populations (Bartholomew 1973;Taylor 1979;Forsius 1979;Konstas & Allan 1989) and large ophthalmic cohorts (Colin et al 1988;Montanes et al 1989). In the present study no difference was found for sex between the 3 groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two studies where the data were population corrected and subsequently compared with age matched controls, show females being affected by the disorder more frequently than males (Aasved 1969;Hiller et al 1982). However, this preponderance of females has not been confirmed in other populations (Bartholomew 1973;Taylor 1979;Forsius 1979;Konstas & Allan 1989) and large ophthalmic cohorts (Colin et al 1988;Montanes et al 1989). In the present study no difference was found for sex between the 3 groups.…”
Section: Discussionmentioning
confidence: 99%
“…In that study, Lindberg documented changes consistent with the diagnosis of the disorder in 28 out of 142 cataractous patients. Overall, most published reports have suggested a higher prevalence of EXS in cataract patients (Horven 1966;Taylor et al 1977;Roth & Epstein 1980;Madden & Crowley 1982;Forsius 1988;Konstas & Allan 1989). In the Framingham study, however, although an association between exfoliation and lens opacities was found in an age-adjusted population cohort, this was not statistically significant (Hiller et a].…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…The group of patients studied and the diagnostic methods employed have been reported previously (Konstas & Allan 1989). Briefly, 74 Greek patients, who underwent trabeculectomy for chronic open angle glaucoma in the University Eye Department, AHEPA Hospital, Thessaloniki were re-examined using 3 different methods in an attempt to determine the true prevalence of EXG in a Greek population who had undergone trabeculectomy.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore surgery is often indicated in EXG and is often successful in reducing IOP (Jerndal & Kriisa 1974, Konstas & Allan 1989, Konstas et al 1993b). However, the preoperative features and the long term effect of surgery upon the preservation of visual function have yet to be studied prospectively in a large cohort of patients.…”
mentioning
confidence: 99%